2012
DOI: 10.1021/jf303398z
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Method for Analysis of Phenolic Compounds in Buds, Leaves, and Fruits of Black Currant (Ribes nigrum L.)

Abstract: Although the fruits are the economic driver for the black currant industry, the buds and leaves are excellent sources of beneficial phenolic compounds that may contribute to the future value of the crop. In this study, extraction of phenolic compounds for different parts of the black currant plant was optimized, and an efficient method for their separation by HPLC was developed. This allowed the simultaneous quantification of a range of hydroxycinnamic acids, flavan-3-ols, flavonols, and anthocyanins by DAD fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 41 publications
(102 reference statements)
5
71
0
Order By: Relevance
“…All these compounds have been previously reported in the leaves of black currant (Oszmiański et al 2011;Vagiri et al 2012). The results here agree with previous findings of black currant leaves being a rich source of bioactive phenolic compounds, particularly hydroxycinnamic acids, and flavonols as well as procyanidins (Tabart et al 2006;Ehrhardt et al 2013;Vagiri et al 2015;Yang et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…All these compounds have been previously reported in the leaves of black currant (Oszmiański et al 2011;Vagiri et al 2012). The results here agree with previous findings of black currant leaves being a rich source of bioactive phenolic compounds, particularly hydroxycinnamic acids, and flavonols as well as procyanidins (Tabart et al 2006;Ehrhardt et al 2013;Vagiri et al 2015;Yang et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The [23], Cistus ladanifer [24] and Cornus mas and Crataegus monogyna [25]. Literature survey has revealed that plant metabolites like phenolic compounds (simple phenols, phenolic acids, flavonoids, catechins etc.,) play an important role in many of the activities like wound healing, analgesic, anti-inflammatory, anti-oxidant, insecticidal and antimicrobial activity [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, this new method has been strongly implemented in academies in basic research, pharmaceutical and agro-chemical industries to study physical, chemical and biological properties of a great diversity of compounds, as well, and quality control of drugs, foods and natural products. In Table 4 are presented some recent works [139][140][141][142][143][144][145] in which HPLC-MS was efectively used for polyphenol characterization of plants and food with very accurate results.…”
Section: The Use Of Hplc-dad/uv-vis and Hplc-msmentioning
confidence: 99%